Separation of cyclodextrins (CDs) using aqueous two-phase system - Ng, Hui Suan; Mokhtar, Mohd Noriznan; Ariff, Arbakariya; Ling, Tau Chuan (Faculty of Engineering, Universiti Putra Malaysia, 2012)
Separation of three different types of cyclodextrins (CDs) [α-,β-, and γ- CD] were investigated in the polyethylene glycol (PEG) 20000/ dextran T500 aqueous two-phase system (ATPS) with an aim to study the partitioning behavior of CDs in the absence of the CDs producing enzyme, cyclodextrin glycosyltransferase (CGTase). The ATPS developed (7.7% (w/w) PEG 20000, 10.3% Dextran T500, with volume ratio, VR of 4.0 was the optimum ATPS for the sago starch bioconversion of Bacillus cereus CGTase. This preliminary study was useful for the further kinetic studies of the sago starch conversion into CDs by the CGTase in an ATPS. The study showed that all types of CDs exhibit the PEG-rich phase preference with the high partition coefficient (KCD) over time. However, difference in the partition coefficients between these 3 CDs was observed, suggesting that their partitioning behaviour in the ATPS were different as a result of the difference in the hydrophobic interactions with the phase components and solubility of CDs. The exclusive partition of CDs into the PEG-rich phase is beneficial for the extractive bioconversion of starch in ATPS.